L’Île Non Sachant ou la méconnaissance du monde arthurien - Emanuele Arioli (Carnets)
A thirteenth century Arthurian Romance, so far unknown, has invented a new island to propose a new version of the legend of King Arthur. The protagonist’s ancestors shipwrecked and settled on a wild island they called Non Sachant Island. As for the protagonist, he leaves his native island to go to King Arthur’s court, where two bad fairies force him to pursue an illusory dragon. Throughout the story, Non Sachant Island is a distorting prism through which the islanders perceive the outside world and vice versa. This article decode the imaginary in the representation of this island, the social organization of its inhabitants as well as the reasons for this insular choice offering the author a margin of freedom in the tradition of Arthurian literature.